Rubio, Josep E. (2017). Raymond Lulle, le langage et la raison: Une introduction à la genèse de l’Ars - Celia López Alcalde (Enrahonar: Quaderns de Filosofia, 2018)
Rubio, Josep E. (2017) Raymond Lulle, le langage et la raison: Une introduction à la genèse de l’Ars París: Librairie Philosophique J. Vrin, 135 p. ISBN 978-2-7116-2714-1